Nagori Rabuhit Government (1968-2017) - Ahmad Fakhri Hutauruk; Andres M Ginting (Criksetra: Jurnal Pendidikan Sejarah, 2019)
Nagori Rabuhit, located in Gunung Maligas Subdistrict, Simalungun Regency, which was formerly inhabited by Simalungun ethnic groups, became a Javanese ethnic settlement.. Therefore it is necessary to examine more deeply how the establishment of the Nagori Rabuhit government. This research uses historical research methods. The data collection techniques are carried out by: (1) observation, (2) interviews, (3) document studies and (4) literature studies. While the technique of data analysis researchers conducted: (1) heuristics, (2) verification, (3) interpretation and (4) historigraphy. The results of the research show that long before the 1960s the Nagori Rabuhit government was established, but it was an obstacle to determine since what year the government must have been established. This is because there is no written evidence found when it stood and who was the founder of the nagori. The results of the interview also did not show significant results because the interviewees also had not seen written evidence since when the Nagori Rabuhit was established. Along with the times, Nagori Rabuhit became an independent and developed village both in terms of ideology, politics, social, economic, cultural, defense and security. This was also encouraged by the existence of trasnmigran from Java which made Nagori Rabuhit rich in cultural values due to the acculturation process in Nagori.